Diverting Attention Suppresses Human Amygdala Responses to Faces - Morawetz, Carmen; Baudewig, Juergen; Treue, Stefan; Dechent, Peter (Frontiers in Human Neuroscience, 2010)
Recent neuroimaging studies disagree as to whether the processing of emotion-laden visual stimuli is dependent upon the availability of attentional resources or entirely capacity-free. Two main factors have been proposed to be responsible for the discrepancies: the differences in the perceptual attentional demands of the tasks used to divert attentional resources from emotional stimuli and the spatial location of the affective stimuli in the visual field. To date, no neuroimaging report addressed these two issues in the same set of subjects. Therefore, the aim of the study was to investigate the effects of high and low attentional load as well as different stimulus locations on face processing in the amygdala using fMRI to provide further evidence for one of the two opposing theories. We were able for the first time to directly test the interaction of attentional load and spatial location. The results revealed a strong attenuation of amygdala activity when the attentional load was high. The eccentricity of the emotional stimuli did not affect responses in the amygdala and no interaction effect between attentional load and spatial location was found. We conclude that the processing of emotional stimuli in the amygdala is strongly dependent on the availability of attentional resources without a preferred processing of stimuli presented in the periphery and provide firm evidence for the concept of the attentional load theory of emotional processing in the amygdala.